Enhancing Women’s Well-Being: The Role of Psychological Capital and Perceived Gender Equity, With Social Support as a Moderator and Commitment as a Mediator - Chawla, Sonam; Sharma, Radha R. (Frontiers in Psychology, 2019)
The study aims to determine the role of psychological capital and perceived gender equity on employee well-being, particularly women, and assess if commitment mediates and social support moderates the relationships between psychological capital, perceived gender equity, and well-being. A personal survey method was employed for data collection using standardized measures from a representative sample of 433 managers (201 women and 233 men) from private sector companies in India. The findings revealed that perceived gender equity in the workplace positively impacts employee well-being for both men and women, with the greater impact being on women’s well-being. To Facilitate employee well-being, organizations can leverage the strengths of psychological capital through training interventions and can promote perceived gender equity through appropriate policies and practices. This bridges the knowledge gap in developing and utilizing psychological capital to enhance employee well-being, especially for women, who are under pressure due to their demanding multiple roles at work and home.